Tantangan Pengelolaan Keuangan Daerah dalam Mewujudkan Otonomi Daerah yang Berkualitas di Indonesia - Nabia Dilla Derma Pratiwi; Laila Fatia Maharani; Rucy Hayuningrat Arum Puspita; Wilda Efendi Ruslan; Rezky Tania; Nur Hidayah Anggraini; Martika Suci Ristyawati; Enggy Yose (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the major challenges in regional financial management that affect the quality of the implementation of regional autonomy in Indonesia. Regional financial management plays a crucial role in achieving fiscal independence and ensuring the effectiveness of local governance. This research employs a descriptive qualitative method using a literature review approach by examining various scholarly sources, legal regulations, policy reports, and relevant previous studies. The analysis reveals three recurring and interrelated issues: the high level of fiscal dependence of local governments on the central government, the limited capacity and competence of regional financial management personnel, and the persistence of budget misuse reflecting weak governance and oversight mechanisms. These challenges form structural barriers to the realization of fiscal self-reliance and accountable local governance. The study emphasizes that improving regional financial management cannot be carried out in a partial or fragmented manner but requires a comprehensive approach involving the enhancement of human resource capacity, reform of budgeting systems and mechanisms, and the strengthening of transparency and public accountability. Therefore, improving regional financial governance is a strategic step toward achieving effective, sustainable regional autonomy that is oriented toward public welfare.